DICOM re‐encoding of volumetrically annotated Lung Imaging Database Consortium (LIDC) nodules. Issue 12 (1st March 2021) - Fedorov, Andrey; Hancock, Matthew; Clunie, David; Brochhausen, Mathias; Bona, Jonathan; Kirby, Justin; Freymann, John; Pieper, Steve; Aerts, Hugo J. W. L.; Kikinis, Ron; Prior, Fred
Abstract : Published in Medical Physics, Vol. 47, No. 11